2002
DOI: 10.1007/bf02850015
|View full text |Cite
|
Sign up to set email alerts
|

Selective serotonin reuptake inhibitor discontinuation syndrome: A review

Abstract: Selective serotonin reuptake inhibitors (SSRIs) are widely prescribed in the treatment of depression and anxiety, as well as obsessive-compulsive, eating, and impulse-control disorders. Paralleling their widespread use has been an increase in adverse-effect reports not noted during short-term efficacy studies. Significant among these adverse effects is SSRI discontinuation syndrome, which follows the interruption of extended treatment or a reduction in drug dosage and entails somatic and psychological symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…Studies of SSRIs in patients with major psychiatric disorders, for example depression or obsessive compulsive disorder, suggest that SSRIs are potentially associated with certain safety risks, including neurocognitive AEs such as anxiety, hypomania, akathisia and changes in mood [Coupland et al 1996;Khan et al 2003;Tamam and Ozpoyraz, 2002;Zajecka et al 1997]. Systematic analysis of randomized, controlled studies suggested a small increase in the risk of suicidal ideation or suicide attempts in youth [Khan et al 2003] but not in adults [Khan et al 2003;Mann et al 2006].…”
Section: Neurocognitive Safetymentioning
confidence: 99%
“…Studies of SSRIs in patients with major psychiatric disorders, for example depression or obsessive compulsive disorder, suggest that SSRIs are potentially associated with certain safety risks, including neurocognitive AEs such as anxiety, hypomania, akathisia and changes in mood [Coupland et al 1996;Khan et al 2003;Tamam and Ozpoyraz, 2002;Zajecka et al 1997]. Systematic analysis of randomized, controlled studies suggested a small increase in the risk of suicidal ideation or suicide attempts in youth [Khan et al 2003] but not in adults [Khan et al 2003;Mann et al 2006].…”
Section: Neurocognitive Safetymentioning
confidence: 99%
“…If being discontinued, however, SSRIs should be tapered over a 2-week period to avoid SSRI discontinuation syndrome, including dizziness, vertigo, headache, nausea, and insomnia. 74 Of note, bupropion has been associated with minor increases in blood pressure, 73 so blood pressure monitoring is recommended.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Half lives and withdrawal rates of SSRIs are also important in occurrence of withdrawal symptoms. Withdrawal syndrome is more frequently reported especially in SSRIs with a shorter half life such as paroxetine and sertraline (14). Use of SSRIs leads to desensitization in serotonin receptors, resulting in a down-regulation in receptors.…”
Section: Discussionmentioning
confidence: 99%